2000
DOI: 10.1046/j.1464-5491.2000.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

What do patients with diabetes know about their tablets?

Abstract: It is concluded that patients' and professionals' knowledge of oral hypoglycaemic agents is poor. More appropriate advice and information to patients from prescribers may improve patient understanding and hence compliance. Community pharmacists are ideally placed to reinforce this information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 6 publications
3
30
1
2
Order By: Relevance
“…Moreover, one quarter of the subjects on metformin did not take this drug with food, increasing the risk of side effects which could have a negative impact on medication adherence. These results are in agreement with a previous study performed by Browne et al [16]. Our finding, that about one in five type-2 diabetes patients is on insulin treatment, is similar to the portion of insulin users among the participants with diabetes in the National Health and Nutrition Examination Survey (NHANES) conducted in 1999-2000 [12].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, one quarter of the subjects on metformin did not take this drug with food, increasing the risk of side effects which could have a negative impact on medication adherence. These results are in agreement with a previous study performed by Browne et al [16]. Our finding, that about one in five type-2 diabetes patients is on insulin treatment, is similar to the portion of insulin users among the participants with diabetes in the National Health and Nutrition Examination Survey (NHANES) conducted in 1999-2000 [12].…”
Section: Discussionsupporting
confidence: 93%
“…This assumption was supported by the findings that subjects who took their medication at the wrong time were those with less education. Previous studies have shown similar findings [57,63,64]. Another possibility was that wrong advice could have been provided by the healthcare professionals.…”
Section: Medication Self-caresupporting
confidence: 61%
“…Browne (2000) reported 38% of Type 2 diabetes subjects (n = 261) took their OAM incorrectly in relation to food. However, no assessment was done in that study to identify any relationship between wrong timing of OAM with overall glycaemic control [57]. In this study all subjects were prescribed with conventional insulin like Actrapid or Premix 30/70.…”
Section: Medication Self-carementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that people with diabetes have a more difficult time adhering to diet and exercise regimens than to insulin medication administration (Glasgow, McCaul, & Schaffer, 1997;Hentinen & Kyngas, 1992;Ruggiero et al, 1997;Toljamo & Hentinen, 2001). Barriers to medication adherence include complexity of the medication regimen, forgetting to take medication, financial burden, and 14 not understanding the rationale for specific medication regimens (Browne, Avery, Turner, Kerr, & Cavan, 2000;Dunning & Manias, 2005;Nagelkerk, Reick, & Meengs, 2006).…”
Section: Self-regulation Behaviormentioning
confidence: 99%